Design of memory encryption and authentication for secure IoT edge devices - Günay, Recep. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
The security of computer systems has become very important as the Internet of Things (IoT) technology has improved and the number of electronic devices in our daily lives has increased dramatically. üne particular weakness of these devices is the off-chip memory interface since they are easily accessible. They have been subject to various attacks focusing on this weakness such as cold-boot attack and replay attack. Most of the solutions in the literature try to solve this issue by memory encryption and memory authentication with high performance and high hardware cost using cryptography algorithms like AES and SHA. A secure memory solution with memory encryption and authentication with low area and power consumption cost is designed in this thesis. ASCON, a finalist in the NIST lightweight cryptography standardization contest, is used for encryption and hash function. Using a single hardware block for both functions reduces the hardware cost with respect to the literature. A system on chip (SoC) is designed consisting of a secure memory controller with ASCON and metadata cache, key generation block with a built-in true random number generator (TRNG), and secure on-chip storage slots around the open-source RISC-V processor PICORV32. The performance and power costs of encryption and authentication are reduced by applying cache snoops during re-encryption and tree traversal. The SoC is designed in Verilog and implemented in FPGA for hardware verification. It has low area and power consumption overhead with reasonable storage overhead and acceptable performance reduction for IoT applications. NOTE Keywords : Digital circuits, Integrated circuits, Logic circuit, Data encryption.
Keywords: Internet of things.; Digital integrated circuits.; Logic circuits.; Data encryption (Computer science)